2022
DOI: 10.1200/go.22.00123
|View full text |Cite
|
Sign up to set email alerts
|

The Armed Conflict and the Impact on Patients With Cancer in Ukraine: Urgent Considerations

Abstract: On February 24, 2022, a war began within the Ukrainian borders. At least 3.0 million Ukrainian inhabitants have already fled the country. Critical infrastructure, including hospitals, has been damaged. Children with cancer were urgently transported to foreign countries, in an effort to minimize interruption of their life-saving treatments. Most adults did not have that option. War breeds cancer—delaying diagnosis, preventing treatment, and increasing risk. We project that a modest delay in care of only 4 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
3
22
0
1
Order By: Relevance
“…15 , 16 It has been estimated by members of the global oncology community that diagnostic and therapeutic delays in Ukraine for even 4 months could result in an excess of 3600 deaths in coming years from the five most common cancer types. 10 Four of these five (lung, breast, gynaecological, colorectal) are also the most common cancer types involved in clinical trials as demonstrated by this current study. For many of these patients, clinical trials offer an important pathway to accessing the best available therapies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…15 , 16 It has been estimated by members of the global oncology community that diagnostic and therapeutic delays in Ukraine for even 4 months could result in an excess of 3600 deaths in coming years from the five most common cancer types. 10 Four of these five (lung, breast, gynaecological, colorectal) are also the most common cancer types involved in clinical trials as demonstrated by this current study. For many of these patients, clinical trials offer an important pathway to accessing the best available therapies.…”
Section: Discussionsupporting
confidence: 53%
“…The conflict in Ukraine has led to the disruption of these trials both directly and indirectly. 10 This has affected both patients and staff, which subsequently has effects on the research effort and the ability to answer important research questions.…”
Section: Discussionmentioning
confidence: 99%
“…War delays cancer diagnoses, preventing treatment, and increasing risk. War exposes vulnerable patients with cancer to infections and threatening conditions [ 27 ]. It can be supposed that a part of Ukrainian citizens did not have the possibility to continue the oncological treatment at home, or that due to the current military operations in Ukraine, it was not possible to undertake effective diagnostics and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As Caglevic et al powerfully state, "war breeds cancer-delaying diagnosis, preventing treatment, and increasing risk (12)." Hospitals often redirect care to trauma victims, leaving fewer resources available to manage medically fragile patients with cancer or other serious illness (13).…”
Section: Palliative Cancer Care In Humanitarian Emergencies and Crisesmentioning
confidence: 99%